The Bohol Chronicle: Case Study of A Succesful Community Paper - Maslog, Crispin (Silliman Journal, 2024)
In a country where the community press is weak and unstable, the success story of the Bohol Chronicle is an inspiration. In 16 years, the paper rose from nothing to P 200,000. The most important reason for this success is the talent and dedication of the paper’s publisher and editor.